Сравнительная оценка методов определения направления прихода сигналов на основе выборочной корреляционной матрицы - Москалец, Николай Вадимович (НТУ "ХПИ", 2017)
Проводится оценка теоретической предельной разрешающей способности некоторых методов определения направления прихода сигнала, реализованных на основе выборочной корреляционной матрицы. Представлена сравнительная характеристика методов с оценкой достоинств, недостатков и присущих им ограничений. Расчет разрешающей способности методов проведен на основе различных значений параметров сигнально-помеховой обстановки. Полученные результаты имитационного моделирования разрешающей способности методов определения направления прихода сигналов могут быть использованы при выборе эффективного метода в задачах пространственно-временного доступа в соответствии с заданными параметрами сигнально-помеховой обстановки при определенных ограничениях.

Six methods are considered in the analysis of the methods of angular superresolution of the signals: non-adaptive beamforming (Bartlett), Сapon (MVDL), thermal noise (TNA), Borgiotti-Lagunas (B-L), maximal entropy (MEM) and multiple signal classification (MUSIC). The comparative characteristic of the methods with assessing their advantages disadvantages and limitations is given. Theoretical resolution of these methods is assessed in the article. Numerical evaluation of resolution ability of the methods of direction arrival of the signal are obtained based on the simulation of various scenarios of signal-to-noise ratio, taking into account the use of correlated and uncorrelated signals, a different number of antenna elements and the values of the signal / interference + noise ratio. These estimations show the ultimate theoretical accuracy of the methods and the potential for their use in problems of space-time access with set limits. The simulation results confirmed the statistical consistency of these methods of estimation of arrival direction angles of correlated and uncorrelated signals from subscriber stations for the space-time sampling in the output of the linear equidistant antenna array.
Comparative methods of direction of arrival estimation based on a sample correlation matrix
Keywords: пространственно-временной доступ; сверхразрешение; антенная решетка; абонентская станция; пространственно-временной доступ; сверхразрешение; superresolution; space-time access; antenna array